Current Status of Educating Emirati Children with Autism Spectrum Disorder in Dubai - Farooq, Kawthar Mohd Aqil Mohd (2007)
The right of every child in obtaining an education, and studying in any institution is justified. Unfortunately it has not always been the case for children with special needs, including those with Autism Spectrum Disorder (ASD). That right was not given to them until 2006. The purpose of this study was to investigate the current status of education for Emirati children with ASD and what provisions they had in local government schools, as well as in some centres in Dubai. It has also examined different issues related to inclusion in public mainstream schools. Moreover, it has set out to research the effect of any single approach best suited for the individual child. This study has used a qualitative method of investigation, including observation, interviews and document analysis. The data analyzed showed that, the provisions for UAE Nationals with ASD in public mainstream schools were non-existence. There were opposite views among top ranking personal of the ministries and the staff of schools, concerning inclusion of such children in regular public schools. As far as approaches were concerned, a combination of different interventions, tailored-made was needed for the individual child taking into consideration his/her strength and weaknesses. This study ended with a research-based recommendation for future practice.